Integration of geomatics acquisition and multi-source data for visualization and documentation of the finds in the Pauciuri archaeological site (Malvito, Calabria, Italy). Issue 1 (1st April 2022) - Artese, S; Crogiez, S; Caputo, F; Taliano Grasso, A; Zinno, R
Abstract: The surveys of the excavation area of the Pauciuri archaeological site, carried out with geomatic techniques, are described. 3D models of the site and of some particularly interesting remains have been obtained. For an early medieval burial both TLS and photogrammetric surveys were carried out, which allowed the development of two 3D models. The comparison between the two techniques has been made: the results are discussed.